The Beautiful Lesson of the I - Hadas, Rachel (Utah State University, University Libraries, 2005)
May Swenson Poetry Award Volume 9, with foreward by Rachel Hadas. Frances Brent's poems have appeared in The New Yorker, Notre Dame Review, Yale Review, and in many other journals. She was born in Chicago and was educated at Barnard College. She studied poetry at Columbia University and the University of Illinois, Chicago. From 1984-1991 she co-edited the literary journal Formations. In 1987 she co-translated Beyond the Limit: poems by Irina Ratushinska-ya She has taught at Yale, Northwestern, Loyola University, and Barat College. She lives with her family in New Haven.